1984
DOI: 10.1677/joe.0.1030363
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in plasma concentrations of steroids during the sensitive period for brain differentiation in the zebra finch

Abstract: Changes in plasma concentrations of sex steroids were examined in male and female zebra finch chicks during the sensitive period for differentiation of sexually dimorphic brain nuclei associated with the control of song. Using a chromatographic separation procedure and radioimmunoassay, androstenedione, testosterone and 5 alpha-dihydrotestosterone were detected in plasma at relatively high concentrations immediately after hatching. There were no sex differences in concentrations of these androgens. An oestroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(78 citation statements)
references
References 29 publications
3
75
0
Order By: Relevance
“…Moreover, estrogen levels were unrelated to body weight or body fat content, suggesting that these are unimportant determinants of circulating estrogens (20). Thus, we have confirmed previous reports that estrogens circulate at comparable levels in adult males and females (7,8) and are not reduced following castration of adult males (8).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, estrogen levels were unrelated to body weight or body fat content, suggesting that these are unimportant determinants of circulating estrogens (20). Thus, we have confirmed previous reports that estrogens circulate at comparable levels in adult males and females (7,8) and are not reduced following castration of adult males (8).…”
Section: Resultssupporting
confidence: 92%
“…Because other tissues lack this enzyme, we conclude that the telencephalon is also the most likely source of estrogens that are found to circulate at high levels in blood of male songbirds (7)(8)(9)(10)(11). This idea is supported further by the observation that levels of both telencephalic aromatase and plasma estradiol are low in nonpasserine birds (17,21,23,27,28).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Three studies have used radioimmunoassays to investigate whether sex differences in plasma hormones exist during development. In the first (Hutchison et al, 1984), E2 and three androgens (T, androstenedione [AE] and DHT) were measured on post-hatching days 1-10. E2 concentrations increased in males from days 2-4, and then by day 10 had declined to those present on day 1.…”
Section: Descriptive Studiesmentioning
confidence: 99%
“…However, these welldocumented effects are difficult to reconcile with several characteristics of E-provision. In the zebra finch, neither circulating E (Adkins- Regan et al, 1990;Schlinger and Arnold, 1992; but see Hutchison et al, 1984), neural aromatase transcription (Shen et al, 1995;Saldanha et al, 1998), nor neural aromatase activity (Vockel et al, 1988(Vockel et al, , 1990Schlinger andArnold, 1991, 1992;Saldanha et al, 1998) has been found to differ between males and females. Lastly, somal aromatase expression is not dimorphic (Saldanha et al, 2000;Peterson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%